2006
DOI: 10.1299/jsmec.49.334
|View full text |Cite
|
Sign up to set email alerts
|

Machinability of Intermetallic Compound Fe3Al from the Viewpoint of Tool Wear

Abstract: The intermetallic compound Fe 3 Al was processed by a reactive sintering process, and its machinability from the viewpoint of tool wear was investigated using dry turning. In cutting Fe 3 Al with a cemented carbide tool, the tool life was approximately one tenth that of cutting carbon tool steel SK3 because of intense flank wear. The tool life for cutting Fe 3 Al using the cemented carbide P20 (WC-TiC-TaC-Co) tool was longer than for cemented carbide K10 (WC-Co). In addition, a cermet tool reached its tool lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Our previous work on cutting Fe-Al intermetallic compounds (Sasaki and Yakou, 2006) showed that the wear of a P-type (WC-TiC-TaC-Co) cemented carbide tool is lower than that of a K-type (WC-Co). Therefore, a throw-away P20 type tool, as shown in Fig.…”
Section: Cutting Testmentioning
confidence: 96%
“…Our previous work on cutting Fe-Al intermetallic compounds (Sasaki and Yakou, 2006) showed that the wear of a P-type (WC-TiC-TaC-Co) cemented carbide tool is lower than that of a K-type (WC-Co). Therefore, a throw-away P20 type tool, as shown in Fig.…”
Section: Cutting Testmentioning
confidence: 96%
“…Machining of iron aluminides by all standard techniques such as grinding, turning, threading, and drilling has been demonstrated (272)(273)(274). However, "iron-aluminum alloys tend to work harden" and thus "sharp tools and slow speeds are required" (25, appendix A, p. 2).…”
Section: Machiningmentioning
confidence: 99%